Inhibitory activity and mechanism of calycosin and calycosin-7-O-β-D-glucoside on α-glucosidase: Spectroscopic and molecular docking analyses. (July 2022) - Han, Lingling; Song, Jiaqi; Yan, Chaoqun; Wang, Chunqiang; Wang, Liwei; Li, Wen; Du, Yan; Li, Qingshan; Liang, Taigang
Abstract: Inhibition of α-glucosidase activity plays a key role in reducing blood glucose level of type Ⅱ diabetic patients. In study, the inhibitory activity and mechanism of Calycosin (CA) and calycosin-7- O -β-D -glucoside (CAG), active components from Astragalus membranaceus, against α-glucosidase were studied by α-glucosidase activity tests, spectral analysis and docking simulation studies. The results suggested that the α-glucosidase inhibitory activity of CA (IC50 =39.45 μM) and CAG (IC50 =174.04 μM) were superior to acarbose (positive drug, IC50 =471.73 μM). Fluorescence data indicated that CA and CAG quenched the fluorescence of α-glucosidase by spontaneous forming CA-α-glucosidase and CAG-α-glucosidase complexes. Besides, results obtained from CD and FT-IR analysis showed that the binding of CA or CAG to α-glucosidase caused conformational changes of α-glucosidase. Docking simulation results further suggested that, compared with CAG, CA had higher affinity for α-glucosidase because of its tightly bound to residues in active cavity of α-glucosidase. These findings demonstrated the α-glucosidase inhibitory activity and mechanism of CA and CAG, moreover, provided the basis for structural modification of AM flavonoids in the treatment of diabetes mellitus. Graphical Abstract: ga1 Highlights: Calycosin (CA) and calycosin-7-O-β-D -glucoside (CAG) interacted with α-glucosidase. Hydrophobic interaction was a main force to stabilize ligand-enzyme complex. CA and CAG changed the conformation and secondary structure of α-glucosidase. CA exhibited a stronger binding affinity than CAG toward α-glucosidase.